OFFSET
0,4
COMMENTS
Let d(n) = Sum_{k = 0..n} (-1)^k*binomial(n,k)^3. Clearly, by symmetry of the binomial coefficients we have d(2*n + 1) = 0. Dixon's identity is the result d(2*n) = (-1)^n*(3*n)!/n!^3. A generalization is: for r a nonnegative integer there holds Sum_{k = 0..n} (-1)^k*binomial(k,r)^3*binomial(n,k)^3 = (-1)^r*binomial(n,r)^3*d(n - r). This is the case r = 1. See A273631 (case r = 2) and A245086 (case r = 0).
LINKS
Peter Bala, A generalization of Dixon's identity
J. Ward, 100 Years of Dixon's Identity, Irish Mathematical Society Bulletin 27, 46-54, 1991
Wikipedia, Dixon's identity
FORMULA
MAPLE
seq(add((-1)^k*k^3*binomial(n, k)^3, k = 0..n), n = 0..30);
MATHEMATICA
Table[Sum[(-1)^k*k^3 Binomial[n, k]^3, {k, 0, n}], {n, 0, 27}] (* Michael De Vlieger, Jul 22 2016 *)
PROG
(PARI) a(n) = sum(k=0, n, (-1)^k*k^3*binomial(n, k)^3) \\ Felix Fröhlich, Jul 22 2016
(Magma) [&+[(-1)^k*k^3 *Binomial(n, k)^3: k in [0..n]]: n in [0..70]]; // Vincenzo Librandi, Jul 23 2016
(Python)
from math import factorial
def A273630(n): return (1 if (m:=n>>1)&1 else -1)*n**3*factorial(3*m)//factorial(m)**3 if n&1 else 0 # Chai Wah Wu, Oct 04 2022
CROSSREFS
KEYWORD
sign,easy
AUTHOR
Peter Bala, Jul 17 2016
STATUS
approved